Dance Rhythms Improve Motor Symptoms in Individuals with Parkinson's Disease: A Randomized Clinical Trial - Moratelli J.A.* (2022)
© 2022 SAGE Publications.Background: Evidence-based practices involving dance modalities found in binary (two-beat rhythm) or quaternary (four-beat rhythm) show that dance positively influences the motor aspects of disease. Aim: This randomized clinical trial aimed to analyze the effect of two dance rhythm (binary and quaternary) on the balance, gait, and mobility in individuals with Parkinson's disease (PD). Methods: Thirty-one individuals with PD were randomized into the binary group (n = 18) and the quaternary group (n = 13). Both groups participated in different dance rhythms lasting 12 weeks, twice a week, for 45 minutes. Results: The binary group showed a significant difference in balance (p = 0.003), freezing of gait (p = 0.007), as well as in the motor aspects of MDS-Unified Parkinson's Disease Rating Scale (MDS-UPDRS), with emphasis on the total values with a score change of 3.23. In the quaternary group, significant differences were found in balance (p = 0.021) with a score change of -2.54 and in the motor aspects of the MDS-UPDRS Part III where the total values stood out with a change of 3.54. Discussion: When comparing the possible effects of binary and quaternary rhythms on the motor symptoms of individuals with PD, it was demonstrated that binary rhythm improved balance, freezing gait, and UPDRSIII. As for the quaternary rhythm, the benefits were in balance and the UPDRSIII. Conclusion: The binary and the quaternary rhythm dance protocols positively influenced the motor symptoms of individuals with PD after 12 weeks of intervention.